Artérias da coxa de Cebus Libidinosus (Rylands, 2000) - Pfrimer, Gabriel de Abreu (2013)
The Cebus libidinosus (Cl), also known as monkey, is a New World primate easily found in South American continent. The objective of this work is to describe the main arteries of the thigh Cl these being the femoral artery , deep femoral , popliteal and medial and lateral femoral circumflex . Eight were dissected C.L. fixed in formalin 10% and 5 % glycerin . The arteries of the thigh were described as to the origin , divisions , and distribution path and the results were compared with the literature of primates . The femoral artery is the larger caliber observed in the thigh . Has its onset after the passage of the external iliac artery through the foramen inguinal region proximal femur bone . The division of the femoral artery and popliteal saphenous occurred in the distal third of the thigh , near the popliteal fossa , continuing its path in the leg . The medial femoral circumflex artery may originate both from the obturator artery as the femoral artery . However , its path , regardless of its origin , is in the caudal region of the pubic bone to the proximal third of the femur bone , mainly vascularizing gracilis , adductor magnus , adductor and pectineus short . The lateral femoral circumflex artery has its origin from the femoral artery and divides, in the proximal femur bone in the ascending branch and descending branch , which are distributed in the cranial region of the thigh . The deep femoral artery is a branch of the external iliac artery , has wide distribution in the cranial and caudal thigh , and the final portion of the artery divides into just a perforating branch . In comparison with the Old World primates it was concluded that the origins of the arteries branching distributions and studied thigh Cl was not equal to a known primate . However, the minor similarities occurring near the Cl the pattern of baboons , probably because both have same habits tail and locomotion on the ground .